A multiwavelength photometric census of AGN and star formation activity in the brightest cluster galaxies of X-ray selected clusters. Issue 1 (7th June 2016) - Green, T. S.; Edge, A. C.; Stott, J. P.; Ebeling, H.; Burgett, W. S.; Chambers, K. C.; Draper, P. W.; Metcalfe, N.; Kaiser, N.; Wainscoat, R. J.; Waters, C.
Abstract: Despite their reputation as being 'red and dead', the unique environment inhabited by brightest cluster galaxies (BCGs) can often lead to a self-regulated feedback cycle between radiatively cooling intracluster gas and star formation and active galactic nucleus (AGN) activity in the BCG. However the prevalence of 'active' BCGs, and details of the feedback involved, are still uncertain. We have performed an optical, UV and mid-IR photometric analysis of the BCGs in 981 clusters at 0.03 < z < 0.5, selected from the ROSAT All Sky Survey. Using Pan-STARRS PS1 3π, GALEX and WISE survey data we look for BCGs with photometric colours which deviate from that of the bulk population of passive BCGs – indicative of AGN and/or star formation activity within the BCG. We find that whilst the majority of BCGs are consistent with being passive, at least 14 per cent of our BCGs show a significant colour offset from passivity in at least one colour index. And, where available, supplementary spectroscopy reveals the majority of these particular BCGs show strong optical emission lines. On comparing BCG 'activity' with the X-ray luminosity of the host cluster, we find that BCGs showing a colour offset are preferentially found in the more X-ray luminous clusters, indicative of the connection between BCG 'activity' and the intracluster medium.